Export Discoveries, Diversification and Barriers to Entry - Klinger, Bailey (2012)
The literature on the relationship between economic diversification and development established that diversification rises with development up to a point. Some have argued that market failures reduce private investments that are necessary to find out whether a new product can be exported profitably, thus implying that the threat of entry can reduce export discoveries and consequently hamper diversification. In parallel, the trade literature on the "extensive margin" of trade has focused on the role of fixed costs of exporting, which affects the number and types of firms that enter into exporting activities. This article presents data suggesting that export diversification and export discoveries are correlated over the course of development, and it provides an empirical test of market failures that might deter export discoveries. The findings suggest that the threat of entry by imitators reduces the number of export discoveries within countries and industries for a given rate of growth of non-discovery exports. However, this market-failure effect is less pronounced when allowing for inter-industry spillovers, whereby export discoveries in one industry lead to discoveries in another industry. The policy implication is that barriers to entry should not be used to protect innovators from the threat of imitation, but governments could consider interventions that directly focus on stimulating export discoveries.